Correlations of flavonoids content and antioxidant activity in bee honey from Bosnia and Herzegovina - Tahirovića, Ismet; Smječanin, Narcisa; Zehrina Bajramović; Amira Čopra-Janićijević; Muamer Dizdar; Kurtagić, Harun; Aldina Aldžić-Baltić; Jasmin Toromanović; Nermin Buza (Emirates Journal of Food and Agriculture, 2023)
In this study, it was performed identification and quantification of flavonoids (apigenin, chrysin, hesperetin, kaempferol, luteolin, naringenin, and quercetin) and flavonoid glycosides (rutin and vitexin) in total 49 samples of five different honey types from Bosnia and Herzegovina: meadow honey (MH, 22 samples), forest (FH, 10), acacia (AH, 7), chestnut (CH, 5), and heather honey (HH, 5). Additionally, evaluation of correlations between FC and total hydrophilic antioxidant score (antioxidant activity against both: ROO· + OH·) in supernatants (s) and in bulk (noncentrifuged) solution (b) of these honey types was performed. Moreover, correlations between flavonoids content (FC) and previously reported antioxidant activity against both peroxyl and hydroxyl free radicals (AC(ROO·) and AC(OH·)) for the same honey samples was examined. High performance liquid chromatography with photodiode array detector (HPLC-DAD) and isocratic elution mode was used as method of analysis. Flavonoids were extracted by solid phase extraction (SPE). The average contents of three flavonoids (chrysin, naringenin, and luteolin) in MH were statistically higher than in AH (p**<0.01). Also, the average content of naringenin in FH was statistically higher than in CH (p*<0.05). We observed a high (positive) linear correlation between FC and AC(ROO·) in s of four honey types (FH, AH, HH, CH) (R2=0.920). If we correlate FC and AC(ROO·)s of three honey types (FH, AH, HH), linearity is very high (R2=0.968), and for FH, AH, CH linearity is complete. The correlation between FC and AC(ROO·) in b of the same honey types is similar, but lower. The correlation does not exist between FC and AC(OH·) neither in s nor in b of five or four honey types, but for FC to both (AC(OH·)s and AC(OH·)b) of three honey types (FH, AH, CH), linearity is moderate (R2=0.732 and R2=0.696, respectively). Keywords: antioxidant activity, correlations, flavonoids, honey, HPLC-DAD.